2020
DOI: 10.1063/5.0026878
|View full text |Cite
|
Sign up to set email alerts
|

Sessile drop response to a single wave electrokinetic excitation

Abstract: The response time for maximum drop deformation and its comparison with different time scales is established and verified with experiments. The applied fluctuation is achieved by applying a single wave perturbation of electrowetting with desired amplitude and frequency. To pinpoint the importance of the initial actuation conditions, the variance in the maximum drop deformation for a single wave perturbation is studied. The focus of this study was to analyze the maximum deformation of a drop for a wide range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…The viscous dissipation, spreading momentum caused by external triggering, and interfacial energies dictate the oscillatory behavior. We have studied this oscillation-damping effect in our previous paper . The change in the magnitude of the bridge height and the frequency of oscillatory motion is associated with the underdamped regime, in which the drop oscillates and the magnitude of these oscillations decay exponentially over time , until steady state is reached.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The viscous dissipation, spreading momentum caused by external triggering, and interfacial energies dictate the oscillatory behavior. We have studied this oscillation-damping effect in our previous paper . The change in the magnitude of the bridge height and the frequency of oscillatory motion is associated with the underdamped regime, in which the drop oscillates and the magnitude of these oscillations decay exponentially over time , until steady state is reached.…”
Section: Resultsmentioning
confidence: 99%
“…The drops consisted of aqueous solutions of glycerol and 0.1 M sodium chloride. The properties of the liquids used as the droplet and surrounding medium at room temperature are presented in Table I in the Supporting Information . Charges at the bottom copper substrate, and the ions and their associated charges, which are generated on the dielectric substrate and droplet interfaces when the electric field is applied to aqueous droplets is illustrated in Figure (a)­(ii)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drop oscillation dynamics on a thin liquid film is related to many natural applications such as in enhancing condensation, water harvesting, liquid infused surfaces (LIS), and drop impact dynamics. In particular, recent studies have shown that drop oscillation, induced by surface vibrations, enhances the mobility of sessile drops and the pinching dynamics of pendant drops. When the forcing frequencies match the natural frequencies of the drops, the oscillation reaches a resonant state, maximizing the excitation amplitude. The high amplitude at the resonant state leads to longitudinal or lateral drop motion, generating contact line movement. Yao et al showed that oscillating drops at the first resonant frequency, as opposed to the second resonant frequency, allowed for drops to overcome contact angle hysteresis and enhanced drop mobility .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the liquid viscosity is an important parameter affecting the performance of EWOD-based liquid handling. Marin Quintero and Waghmare 43 found that the deformation response of sessile droplets in EWOD is affected by both the system viscosity and the electrical signal parameters. However, the effects of liquid viscosity on the formation, propagation, and attenuation of EWCWs have not yet been reported.…”
Section: ■ Introductionmentioning
confidence: 99%